Peran Pendidikan Islam dalam pembentukan karakter di Era milenial - Zahro, Suaidatuz (Maliki Interdisciplinary Journal, 2026)
The rapid advancement of technology and globalization in the millennial era has significantly impacted the character development of young generations. Unlimited access to information often brings challenges, including moral degradation, identity shifts, and the infiltration of values that contradict Islamic teachings. Islamic Religious Education (IRE) plays a crucial role in strengthening the moral and spiritual foundation of millennials by intregating Islamic values through cognitive, affective, and psychomotor learning processes. This study employs a literature review method by analyzing various relevant scholarly sources to explore how IRE contributes to shaping millennial character in the digital age. The findings indicate that IRE serves as a moral guide, a reinforcement of religious identity, and a driver of positive behavior, enabling millennials to become individuals with integrity, responsibility, and the ability to adapt to modernization while maintaining Islamic priniples.